Persepsi Wajib Pajak pada Pembingkaian Pemberitaan Kasus Penghindaran Pajak dalam Keputusan Kepatuhan Pajak - Auril, Titania; Angriani, Elda; Nanda, Nanda; Ikhsan, Syarbini (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Framing causes individuals to have different behavior in making various decisions. In this research, the framing of tax avoidance news is one of the factors in taxpayers' perceptions of whether or not they will remain compliant with taxes after reading tax avoidance news. This research aims to find out how taxpayers perceive the framing of tax avoidance news in tax compliance decisions using the Theory of Planned Behavior (TPB) and the Theory of Reasoned Action (TRA) which are used as a basis for explaining changes in individual behavior when receiving the framing effect. This descriptive research was carried out by collecting primary data on the population, namely taxpayers in Pontianak City, West Kalimantan. This research data was collected from May to June 2023. Data was collected using interview techniques. Respondents in this study were selected using a purposive sampling technique. The findings in this research are the perception that taxpayers still choose to comply with taxes after hearing news about tax avoidance, which means that taxpayers think that news about tax avoidance is framed positively.